Synthesis of gold hydrosols in the presence of Na2EDTA - Shevchenko, Gvidona P.; Zhuravkov, Victor A.; Osipovich, Nikolaj P.; Shishko, Galina V. (Journal of the Belarusian State University. Chemistry, 2019)
The possibility of  Na2EDTA applying as a reducing and stabilizing reagent in aqueous medium to obtain gold hydrosols from hydrogen tetrachloroaurate was studied. It was found that, depending on the pH of the reaction medium, both nanosized precipitates (~60 nm) and gold hydrosols, consisting of spherical nanoparticles of uniform size (12–15 nm), can be obtained. Stable gold sols are formed at pH ≥ 10.5. Sol formation process rate depends on the temperature and concentration of  Na2EDTA and increases with their increase. An electrochemical study of processes of  HAuCl4 reduction and Na2EDTA oxidation showed that the possibility of gold hydrosols formation in an alkaline medium is due to the kinetic inhibition of the reduction process of gold hydroxo complexes formed during this process.
Keywords: gold nanoparticles; gold hydrosols; reduction of hydrogen tetrachloroaurate; Na2EDTA